Growth effect of foreign direct investment and innovative activity in developing countries - Nordin, Nurnaddia (2017)
This dissertation focuses on three important issues which are related to growth performance and innovative activity in developing countries. This study is strongly driven by recent literature which reveals ambiguous findings on the factors which influence economic performance across countries. The first objective of this study is to analyse the role of labour mobility in moderating the impact of foreign direct investment (FDI) on economic growth. It tests whether countries with high level of labour market flexibility can benefit from FDI inflows more efficiently. It uses panel observations from 80 developing countries spanning over the 2000-2012 period. Threshold regression was employed to examine the influence of labour market flexibility on the impact of FDI on output growth. This methodological approach is chosen because it is flexible enough to accommodate the possibility that the impact of FDI “kicks in” only after host countries have achieved a certain level of labour market flexibility. The result suggest that there is a threshold effect in the FDI-growth relationship such that the positive impact of FDI kick in only after host countries achieve a certain level of quality in term of labour market flexibility. This finding is consistent with the view that host countries must have absorptive capacity in order to benefit from FDI inflows. Therefore, policymakers should weigh the cost of policies aimed at attracting FDI versus those that seek to improve the flexibility of labour market. The second objective of this study is to examine factors that influence innovation in developing countries. To evaluate this objective, a sample of 52 developing countries is used over the 2000-2010 period. The generalized method of moments (GMM) panel estimator is employed to test this objective. Generally, there are six factors examined in this study namely, human capital, regulation, trade openness, trademarks, patents and stock market. The empirical results reveal that trade openness, patent and human capital are important in influencing innovation activity in developing countries. Among these factors, trade openness appears to be the most important determinant. This suggests that developing countries are able to further enhance their innovation activity with more trade. Thus, the government should focus on promoting trade liberalization because it is expected to bring tremendous benefits for innovation community. Moreover, investments in human capital development by providing education and training and also improvement in patent protection will also benefit domestic innovation. Finally, the third objective of this study is to examine the role economic freedom plays in R&D spillovers (i.e. the impact of research and development activity (R&D) on total factor productivity (TFP) for the ASEAN-5 countries. The dynamic ordinary least square (DOLS) panel estimator is employed using data from 1996 to 2012. There are three important conclusions that can be drawn from the reported results. First, foreign R&D is more important for productivity improvements than domestic R&D. Second, import is the main channel for international R&D spillovers. Third, economic freedom plays an important role in moderating both domestic and foreign R&D spillovers. Therefore, policymakers and government should play an important role in promoting trade liberalization and other policies that enhance freedom of economic activities as both are expected to boost domestic productivity.